UNSUR KEMASLAHATAN PADA HIBAH SUAMI – ISTRI - Muhammad Zainuddin Sunarto (Fakultas Syariah - IAI Al-Qolam Malang, 2020)
Grant practice is a transaction that is commonly done by the community. Apart from that, the grant is a sunnah work that is highly recommended carried out by Muslims. The Compilation of Islamic Law (KHI) and the Civil Code (KUHPerdata/BW) have governed the implementation of grants in Indonesia. basically the purpose of the grant between husband and wife to improve the quality of family relationships that love each other. However, not all good intentions and objectives have good consequences, moreover the actions taken are not based on careful calculation. Grants between husband and wife in the Compilation of Islamic Law are permitted. That is because there are no provisions that state who is entitled or not entitled to receive or give grants. While regarding the grants between husband and wife, the Civil Code said differently. In the Civil Code, grants between husband and wife during marriage are prohibited.